Kuliah Kerja Nyata Sebagai Wujud Pemberdayaan Masyarakat Desa Minasa Baji Di Masa Pandemi Covid-19 - Yuni Kartini; Muh. Nurhasbi; Jihan Zhafira; Sintardina Yunus; M. Alfian Saeni; Firmansyah Firmansyah; Safitri Safitri; Lisa Lestari Anriani; Miftahul Jannah; Andi Ayu Anisa; Linda Linda; Yuniar Israeni; Firda Firda; Karman Karman; Haeril Inzaghi; Hasriani Hasriani (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
The implementation of the Real Work Lecture (KKN) carried out by Maros Muslim University students as a form of community service aims to awaken and empower the Minasa Baji village community in the midst of the COVID-19 pandemic. In the COVID-19 pandemic situation, people really need encouragement and motivation to help change their mindset to be productive again. The method used in this service is to convey the material orally to the Minasa Baji village community. The results of community service, namely through the environmentally friendly village work program (KRL), the introduction of online cash book applications, sorting organic and inorganic waste were able to help rural communities get back up in the midst of adversity due to the covid-19 outbreak.